MARKETING STIMULI AND AUTHORS' INTENTIONS TO CHOOSE A PUBLISHER FOR PUBLISHING THEIR BOOKS: THE MEDIATION ROLE OF PERCEIVED USEFULNESS - Rahayu, Elisa Dwi; Anjaningrum, Widiya Dewi (Jurnal Apresiasi Ekonomi, 2024)
The indie publishing industry faces many challenges in the digital era. Therefore, every publisher must be able to find the determining factor in attracting authors to publish their books. This study aims to determine the strength of the impact of marketing stimuli on purchasing intentions mediated by perceived usefulness. A total of 150 participants of the "Book Writing Camp" at PT. Litera Media Tama has been selected using purposive sampling techniques. Quantitative research using online questionnaires has been conducted for one month. The results of the second-order PLS-SEM analysis prove all hypotheses, where marketing stimuli strongly impact the intention of authors to publish their books at the Litera Media Tama publisher if the author feels high perceived usefulness. In other words, the mediating role of perceived usefulness felt by consumers is significant in the relationship between marketing stimuli and purchasing intentions for publishing services. Further research can be conducted through qualitative studies to explore more in-depth information and expand the respondents, not only from the participants of the "Book Writing Camp" PT. Litera Media Tama and other publishers can partially test each marketing stimulus on purchasing intentions to determine which marketing stimulus positively impacts purchasing intentions for publishing services.